Developing processes for the co-creation and co-governance of urban green space in dense urban areas. A Maltese case study - Scheiber, Sarah; Mifsud, Wendy Jo (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The lack of and inequitable access to recreational and green open space in Malta is clearly documented. In an attempt to address social inequalities, research on place-led experimentation as a co-creation and co-governance process is ongoing. A multiple case study and participant action research methodology through the application of placemaking and urban living lab concepts is adopted. Communities are engaged to rethink public spaces as greener places and foster a better relationship with nature while improving the urban environment through nature-based placemaking. The research strives to understand how residents of Maltese localities can be motivated to participate in bettering their urban environment and foster a sense of pride in their spaces. This paper presents the findings of the locality of Senglea case study. A placemaking toolkit, by Placemaking Europe is adapted, applied and analysed within the Maltese context, consisting of a series of workshops to build a relationship with local communities according to their specific needs and desires. This paper provides insight into some of the key learning outcomes emerging from this first case study. Moreover, it puts forth recommendations on how processes for co-creation and co-governance of public spaces in dense urban areas such as Malta may be developed.